Microgrid advanced control methods and renewable energy system integration - Mahmoud, Magdi S. (Amsterdam Butterworth-Heinemann, 2017)
Microgrids: Advanced Control Methods and Renewable Energy System Integration demonstrates the state-of-art of methods and applications of microgrid control, with eleven concise and comprehensive chapters. The first three chapters provide an overview of the control methods of microgrid systems that is followed by a review of distributed control and management strategies for the next generation microgrids. Next, the book identifies future research directions and discusses the hierarchical power sharing control in DC Microgrids. Chapter 4 investigates the demand side management in microgrid control systems from various perspectives, followed by an outline of the operation and controls of the smart microgrids in Chapter 5. Chapter 6 deals with control of low-voltage microgrids with master/slave architecture. The final chapters explain the load-Frequency Controllers for Distributed Power System Generation Units and the issue of robust control design for VSIs, followed by a communication solution denoted as power talk. Finally, in Chapter 11, real-time implementation of distributed control for an autonomous microgrid system is performed.--Provided by publisher.
Microgrid control problems and related issues -- Distributed control techniques in microgrids -- Hierarchial power sharing control in DC microgrids -- Master/slave power-based control of low-voltage microgrids -- Load-frequency controllers for distributed power system generation units -- An optimization approach to design robust controller for voltage source inverters -- Demand side management in microgrid control systems -- Towards a concept of cooperating power network for energy management and control of microgrids -- Power electronics for microgrids: concepts and future trends -- Power electronic converters in microgrid applications -- Power talk: communication in a DC microgrid through modulation of the power electronics components -- Pilot-scale implementation of coordinated control for autonomous microgrids
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Microgrids (Smart power grids) -- Automatic control; Electronic books